Optimization of Process Parameters for Composting of Pulp/Paper Mill Sludge With Hazelnut Kernel Using a Statistical Method - Aycan, N.; Turan, N.G.; Özgönenel, O. (Technical University of Wroclaw bg@bg.pwr.wroc.pl, 2014)
An effective way to remove ammonium from compost using hazelnut kernels (HK) has been presented. The role of experimental factors on the removal of ammonium was examined by using the full factor experimental design (FFED). The experimental factors and their related levels were selected as time of 1-6 weeks, moisture of 50-70%, and HK amendment ratio of 5-25. The results were then evaluated by the ANOVA test to examine importance of the process variables (inputs) and their levels. A regression model taking into account main significant and interaction effects was suggested. According to the optimization algorithm, time of 5 weeks, moisture of 50%, and HK amendment ratio of 25 with the removal capacity of 60% were selected as optimum levels. The proposed analyzing procedure is simple to implement and cost-effective.